2011
DOI: 10.1002/j.2162-6057.2011.tb01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Training Insight Problem Solving Through Focus on Barriers and Assumptions

Abstract: Recent research has reported successful training interventions that improve insight problem solving. In some ways this is surprising, because the processes involved in insight solutions are often assumed to be unconscious, whereas the training interventions focus on conscious cognitive strategies. We propose one mechanism that may help to explain this apparent disconnect. Recognition of a barrier to progress during insight problem solving may provide a point of access to the tacit constraining assumptions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…However, it differs from other types of domain-specific meta-cognitive training investigated in previous literature (some of which is domain specific, e.g., Walinga et al, 2011; Patrick and Ahmed, 2014; Patrick et al, 2015) in that the participants in the present study were asked to use the “oppositional reasoning” strategy they had been told about in their exploration of the spatial domain. For both of these reasons it can be said to represent yet another method to add to the types of training whose facilitating effects on insight problem solving have been tested.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, it differs from other types of domain-specific meta-cognitive training investigated in previous literature (some of which is domain specific, e.g., Walinga et al, 2011; Patrick and Ahmed, 2014; Patrick et al, 2015) in that the participants in the present study were asked to use the “oppositional reasoning” strategy they had been told about in their exploration of the spatial domain. For both of these reasons it can be said to represent yet another method to add to the types of training whose facilitating effects on insight problem solving have been tested.…”
Section: Discussionmentioning
confidence: 83%
“…The aim of the experiment was to investigate the effects of specific hints or training on insight problem solving. The impact of general meta-cognitive training on performance has been addressed in previous literature (e.g., Walinga et al, 2011; Patrick and Ahmed, 2014; Patrick et al, 2015), as has the impact of more specific hints which have been customized to the contents of a specific problem (e.g., Chronicle et al, 2001, Experiment 3; Weisberg and Alba, 1981; Grant and Spivey, 2003; Kershaw and Ohlsson, 2004; Kershaw et al, 2013; Öllinger et al, 2013, 2014). What we aimed to focus on here, and to further test based on the results of the experiment, was the hypothesis that thinking in contraries might support transformations in the mental representation of a problem, as required by insight problem solving.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few studies have investigated how a cognitive procedure can be designed and trained to facilitate the solution of not only one problem for which the training was designed but also other previously unseen problems. The studies by Ansburg and Dominowski (2000); Chrysikou (2006); Dow and Mayer (2004); Walinga, Cunningham, and MacGregor (2011); and Wicker, Weinstein, Yelich, and Brooks (1978) are of particular interest in this respect because training did not directly cue the nature or category of the test problem(s), and the training was intended to facilitate representation change for a variety of verbal insight problems with different constraints. The study by Chrysikou (2006), using a form of creativity training that involved attempting to break the stereotypical categorization of critical objects, revealed that problem solving improved to approximately 60% irrespective of whether the training included the problem-specific object or not.…”
Section: Training Studies Of Representation Changementioning
confidence: 99%
“…Because these processes require more active and purposeful techniques, it is also easier to teach these strategies through explicit instruction. The research concerning incubation shows mixed results, in terms of the success rates of incubation for laboratory settings (Browne & Cruse, ), although recent research shows moderate success for insight problem‐solving with specific training instructions that focus on the removal of cognitive barriers (Cunningham & MacGregor, ; Walinga, Cunningham, & MacGregor, ). It might not be possible to teach people how to incubate or how to flow, but suggestions can be made for placing oneself into situations conducive to these processes.…”
Section: Discussionmentioning
confidence: 99%